Trapped in Statelessness: Rohingya Refugees in Bangladesh - Milton, Abul Hasnat; Rahman, Mijanur; Hussain, Sumaira; Jindal, Charulata; Choudhury, Sushmita; Akter, Shahnaz; Ferdousi, Shahana; Mouly, Tafzila Akter; Hall, John; Efird, Jimmy T. (My University, 2017)
The Rohingya people are one of the most ill-treated and persecuted refugee groups in the world, having lived in a realm of statelessness for over six generations, and who are still doing so. In recent years, more than 500,000 Rohingyas fled from Myanmar (Burma) to neighboring countries. This article addresses the Rohingya refugee crisis in Bangladesh, with special emphasis on the living conditions of this vulnerable population. We reviewed several documents on Rohingya refugees, visited a registered refugee camp (Teknaf), collected case reports, and conducted a series of meetings with stakeholders in the Cox’s Bazar district of Bangladesh. A total of 33,131 registered Rohingya refugees are living in two registered camps in Cox’s Bazar, and up to 80,000 additional refugees are housed in nearby makeshift camps. Overall, the living conditions of Rohingya refugees inside the overcrowded camps remain dismal. Mental health is poor, proper hygiene conditions are lacking, malnutrition is endemic, and physical/sexual abuse is high. A concerted diplomatic effort involving Bangladesh and Myanmar, and international mediators such as the Organization of Islamic Countries and the United Nations, is urgently required to effectively address this complex situation.